Dicyanovinylnaphthalenes for neuroimaging of amyloids and relationships of electronic structures and geometries to binding affinities - Petric, Andrej; Johnson, Scott A.; Pham, Hung V.; Li, Ying; Ceh, Simon; Golobic, Amalija; Agdeppa, Eric D.; Timbol, Gerald; Liu, Jie; Keum, Gyochang; Satyamurthy, Nagichettiar; Kepe, Vladimir; et al. (NATL ACAD SCIENCES, 2012)
The positron-emission tomography (PET) probe 2-(1-[6-[(2-fluoroethyl)(methyl) amino]-2-naphthyl] ethylidene) (FDDNP) is used for the noninvasive brain imaging of amyloid-beta (A beta) and other amyloid aggregates present in Alzheimer's disease and other neurodegenerative diseases. A series of FDDNP analogs has been synthesized and characterized using spectroscopic and computational methods. The binding affinities of these molecules have been measured experimentally and explained through the use of a computational model. The analogs were created by systematically modifying the donor and the acceptor sides of FDDNP to learn the structural requirements for optimal binding to A beta aggregates. FDDNP and its analogs are neutral, environmentally sensitive, fluorescent molecules with high dipole moments, as evidenced by their spectroscopic properties and dipole moment calculations. The preferred solution-state conformation of these compounds is directly related to the binding affinities. The extreme cases were a nonplanar analog t-butyl-FDDNP, which shows low binding affinity for A beta aggregates (520 nM K-i) in vitro and a nearly planar tricyclic analog cDDNP, which displayed the highest binding affinity (10 pM K-i). Using a previously published X-ray crystallographic model of 1,1-dicyano-2-[6-(dimethylamino) naphthalen-2-yl] propene (DDNP) bound to an amyloidogenic A beta peptide model, we show that the binding affinity is inversely related to the distortion energy necessary to avoid steric clashes along the internal surface of the binding channel.
Keywords: VISCOSITY-SENSITIVE FLUOROPHORE; MOLECULAR-IMAGING PROBE; ALZHEIMERS-DISEASE; IN-VITRO; PLAQUES; MALONONITRILE; DERIVATIVES; INHIBITORS; DESIGN; DDNP